MODERN ISLAMIC EDUCATION REFORM IN TURKEY - Husyein Bayir; Yucel Dilek; Ahmet Bugra (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
This study aims to analyze Islamic education in Türkiye. This includes the first modernizing reforms of the 19th century, which formed the backdrop for the more profound educational reforms of the republican period. Religious education continues to be a very sensitive issue in contemporary Turkish politics. These and other issues (eg, Qur'an courses, compulsory religious education in primary and secondary schools). This study uses a type of qualitative phenomenology. Data collection was carried out by studying literature and documents related to Islamic education in Turkey. The results of this study indicate that the reform of Islamic education in this Turkish educational setting focuses mainly on the impact that Political Islam has, by analyzing the role of religion in various periods of Turkish history. In the 1950s a period of multi-party democracy began in Turkey and the Turkish educational environment was exposed to structural changes at every school level. Islamic leanings are evident in the curricula, the organization of the education system and the appointment of experts throughout the country. Furthermore, subsequent civil administrations, some supported by the military, used Islam as a discourse in education. As a result, Political Islam influences the structure of school curricula, and education policies and their implementation, giving rise to much debate.